The politics of voter suppression defending and expanding Americans' right to vote - Wang, Tova Andrea (Cornell University Press, 2012)
"Tova Wang explains how, across the twentieth century, the issue of access to the ballot was transformed from a largely practical matter of electoral advantage into an ideological difference between the Democrat and Republican Parties."--Publisher's Web site.